Neotectonic structure and evolution of Salamis island - ΜΑΡΙΟΛΑΚΟΣ Η.; ΦΟΥΝΤΟΥΛΗΣ Ι.; ΘΕΟΧΑΡΗΣ Δ. (Bulletin of the Geological Society of Greece, 2001)
The morphotectonic structure that dominate in Salamis Island strike E-W and NE-SW, having as a result that neotectonic grabens and horsts follow these general directions. The asymmetry of the drainage network is due to the kinematic regime of the neotectonic blocks. Salamis Island is located in an area where structural trendings of E-W (Corinthian Gulf, Megara graben, Gerania Mt., Pateras Mt.) and NE-SW (Aigaleo Mt., Ymittos Mt., Athens Basin) are intersected, resulting a complicated neotectonic structure.